Peran dan Sosialisasi Bahasa Daerah Melalui Dunia Digital Pendidikan - Maulid, Taembo; Sari, Mega Puspita; Rahman, Bohri (Yayasan Arrahman Nahdlatul Wathan, 2023)
Motivation is defined as an impetus that moves and directs a person to do something based on what he wants, which is aimed at the goal he wants. IQ (intelligence quotient) itself is a test result that shows the cognitive abilities possessed by individuals to learn new experiences, reason well and solve problems effectively. The discussion about motivation and IQ is quite interesting for many parties, especially when comparing it with success in life, including success in learning language. The results of theoretical studies and previous studies show that both motivation and IQ have a large influence on language learning. However, motivation has more significant effect than IQ in determining the success of language learners. There are several causative factors, namely every language learning always begins with motivation, while IQ is only a support in smooth language acquisition; and motivation has a close relationship with other factors such as self-confidence, high curiosity, optimism, courage, and so on; and language learners who have high IQs but are not motivated to learn languages ​​will tend to be less enthusiastic and not serious.